2016
DOI: 10.1159/000453208
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Hydrogen Sulfide Attenuates High Glucose-Induced Cardiotoxicity by Inhibiting NLRP3 Inflammasome Activation by Suppressing TLR4/NF-κB Pathway in H9c2 Cells

Abstract: Background/Aims: This study aimed to investigate whether exogenous hydrogen sulfide (H2S) confered cardiac protection against high glucose (HG)-induced injury by inhibiting NLRP3 inflammasome activation via a specific TLR4/NF-κB pathway. Methods: H9c2 cardiac cells were exposed to 33 mM glucose for 24 h to induce HG-induced cytotoxicity. The cells were pretreated with NaHS (a donor of H2S) before exposure to HG. Cell viability, cell apoptosis, intracellular reactive oxygen species (ROS), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
63
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(74 citation statements)
references
References 46 publications
(50 reference statements)
7
63
0
Order By: Relevance
“…Inflammation is a common feature of various CKDs and is highly involved in the development and progression of CKD. NLRP3 inflammasome is one of the best characterized inflammasomes [27-30]. Recently, accumulating evidence demonstrated that NLRP3 inflammasome contributes to the CKDs [3, 31, 32] and can be activated by the albumin in human proximal tubule cells [4].…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation is a common feature of various CKDs and is highly involved in the development and progression of CKD. NLRP3 inflammasome is one of the best characterized inflammasomes [27-30]. Recently, accumulating evidence demonstrated that NLRP3 inflammasome contributes to the CKDs [3, 31, 32] and can be activated by the albumin in human proximal tubule cells [4].…”
Section: Discussionmentioning
confidence: 99%
“…Inflammasome is essential for one kidney/deoxycorticosterone acetate/salt-induced hypertension in mice [24]. Hydrogen sulfide suppresses high glucose-induced cardiomyocyte inflammation by inhibiting the TLR4/NF-κB pathway and its downstream NLRP3 inflammasome activation [25]. Ang II-induced hypertension is prevented in NLRP3 gene deletion mice but not in ASC deletion mice, indicating that NLRP3 contributes to gestational hypertension independently of ASC-mediated inflammasomes [26].…”
Section: Introductionmentioning
confidence: 99%
“…The inflammasome is a cytoplasmic multiprotein that contains the nod-like receptor protein (Nlrp) family, adaptor protein ASC [9]. It triggers Caspase-1, IL-18 and IL-1β activation to execute inflammatory responses [9, 10]. Nlrp3 inflammasome activation has been detected in nasal mucosa of AR rats [11].…”
Section: Introductionmentioning
confidence: 99%